Change of Pairs Strategy to Improve Student Learning Outcomes in Arabic Language Subjects - Bey, M Tommy (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2025)
Purpose - This study aims to describe the implementation of the Change of Pairs strategy to improve learning activities and Arabic learning outcomes for class IIB students at Darunnajah 14 Nurul Ilmi Islamic Boarding School, Banten, in the 2024/2025 academic year through two-cycle classroom action research.. Design/Methodology/Approach - This research employed Classroom Action Research using the Kemmis and McTaggart cyclical model conducted in two cycles. The subjects were 22 students selected through total sampling. Data were collected through observation, documentation, and achievement tests, then analyzed using percentage analysis and N-Gain calculation based on Hake's formula. Findings - The research results show that student learning activities increased from 99% in the first cycle to 100% in the second cycle, while mastery of learning outcomes improved from 95% to 100%. The N-Gain score of 0.92 falls into the high category (g ≥ 0.70), thereby confirming the high effectiveness of the Change of Pairs strategy in improving Arabic learning outcomes. Research Limitations/Implications - Teachers at Islamic boarding schools are recommended to implement the Change of Pairs strategy in Arabic language teaching. Future researchers may combine this strategy with other learning models such as role play or problem-based learning to explore broader improvement potential.